Comparison of Cochlear Implant Magnets and Their MRI Artifact Size. (10th January 2020) - Todt, I.; Guerkov, R.; Gehl, H. B.; Sudhoff, H.
Abstract : Introduction . Recent developments regarding cochlear implant magnets (e.g., a bipolar diametral magnet) and refined surgical techniques (e.g., implant positioning) have had a significant impact on the relation between cochlear implants and MRIs, making the reproducible visibility of cochlea and IAC possible. MRI scanning has changed from a contraindication to a diagnostic tool. Magnet artifact size plays a central role in the visual assessment of the cochlea and IAC. Objective . The aim of this study is to compare the CI magnet-related maximum artifact sizes of various cochlea implant systems. Materials and Methods . We performed an in vivo measurement of MRI artifacts at 1.5 and 3 Tesla with three cochlear implant magnet systems (AB 3D, Medel Synchrony, and Oticon ZTI). The implant, including the magnet, was positioned with a head bandage 7.0 cm and 120° from the nasion, external auditory canal. We used a TSE T2w MRI sequence on the axial and coronal plains and compared the artifacts in two volunteers for each tesla strength. Results . Intraindividual artifact size differences between the three magnets are smaller than interindividual maximum artifact size differences. 3 T MRI scans, in comparison to 1.5 T MRI scans, show a difference between soft artifact areas. Conclusion . We observed no major difference between maximum implant magnet artifact sizes of the three implant magnet types.